Mapping Research Trends on 21st-Century Problem-Solving Skills in Science Learning: A Literature Review from 2014 to 2023 - Syarful Annam; Amalia Syuzita; Rosi Pratiwi; Yusuf Sarkingobir (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: Problem-solving skills are among the most important competencies of students, especially in the area of science education in the 21st century. Problem-solving skills enhance critical, logical, and creative thinking skills, which are necessary to solve complex real-life problems. This study is intended to identify and analyze research trends with regard to problem-solving skills in science learning from 2014 to 2023. A qualitative bibliometric approach has been used, and the data was collected using Publish or Perish and Dimensions.ai. In total, 200 documents indexed by Google Scholar were analyzed. Research trends, key keywords, and publication patterns were mapped and visualized using the VOSviewer software. The findings indicated that research on problem-solving skills gained consistent interest over the last decade, with the highest number of publications in 2023. Journals were the most common type of publication, followed by proceedings, chapters, and books. Among all publication venues, the Journal of Physics: Conference Series turned out to be the most important, publishing 784 articles and receiving 2567 citations. The most frequent keywords accompanying research in problem-solving are